Legalitas dan Implementasi Wakaf Online Menurut MUI Sumatera Utara: Studi pada Yayasan Darul Waqaf Al-Hadiy - Siregar, Pangundian; Muhibbussabry (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
The implementation of online waqf at the local level currently faces a dual challenge between massive technological adoption and the unpreparedness of legal-administrative aspects. In North Sumatra, although waqf institutions have transitioned to digital platforms, there remains an absence of regional technical fatwas and obstacles in the formal verification of nazhir that may undermine public trust. This study aims to analyze: (1) the perspective of the North Sumatra Indonesian Ulema Council (MUI) regarding the legality of online waqf; (2) the technical implementation at the Darul Waqaf Alhadiy Foundation in Medan City; and (3) the conformity of these mechanisms with both Islamic and positive law. This research employs a juridical-empirical method, with data collected through interviews, documentation, and field observation. The findings indicate that the North Sumatra MUI considers online waqf to be substantively valid as long as it fulfills the essential pillars (rukn al-waqf), although no specific technical guidelines have yet been issued. The Darul Waqaf Alhadiy Foundation has implemented a digital mechanism that fulfills the requirements of electronic sighat (contract), but from the perspective of positive law, the formal legality of the cash waqf nazhir is still under verification by the Indonesian Waqf Board (BWI). The study concludes that although the online waqf mechanism has been fulfilled from a fiqh perspective, formal legalization of nazhir and the issuance of regional technical fatwas are urgently needed to ensure legal certainty and institutional accountability.